The relationship between certain coaching styles and the achievement motivation of high-level players - the motivation to achieve success, the motivation to avoid failure - - baka, fares (sports creativity, 2025)
The study aimed to identify the leadership behavior of football coaches in the Algerian Premier League and its relationship to the achievement motivation of their players, i.e., to search for the most important leadership styles used by the coaches, and the correlation between each style and the motivation to achieve success or the motivation to avoid failure of the players. The researcher used the descriptive method, and to collect the study data and achieve its objectives, the researcher used the Leadership Behavior Scale for Team Sports Coaches prepared by Abu Zaid (1990), which includes eight dimensions that represent in their entirety the leadership behavior of team sports coaches, namely: (training and guidance, social appreciation, motivation, fairness, facilitating athletic performance, participation and democratic behavior, authoritarian behavior, attention to health aspects) and the Willis scale adapted by Allawi (1998) to measure achievement motivation related to athletic competition. The study sample consisted of (6) coaches and (126) players from various professional first division football clubs during the 2012/2013 season. Among the most important findings of the study are the following: - The leadership behavior practiced by the coaches encompasses various dimensions of leadership, with a focus on certain dimensions they deem more important to the training process than others. - There is a relationship between the leadership behavior practiced by football coaches in the first division and the achievement motivation of the players.